Nursery practices in oil palm : a manual /: a manual. (2019) - Laksono, Nur Dian; Setiawati, Umi; Nur, Fazrin; Rahmaningsih, Miranti; Anwar, Yassier; Rusfiandi, Heru; Sembiring, Eben Haeser; Forster, Brian P; Subbarao, Avasarala Sreenivasa; Zahara, Hafni
No abstract available